2007
DOI: 10.1038/sj.npp.1301624
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione Precursor, N-Acetyl-Cysteine, Improves Mismatch Negativity in Schizophrenia Patients

Abstract: In schizophrenia patients, glutathione dysregulation at the gene, protein and functional levels, leads to N-methyl-D-aspartate (NMDA) receptor hypofunction. These patients also exhibit deficits in auditory sensory processing that manifests as impaired mismatch negativity (MMN), which is an auditory evoked potential (AEP) component related to NMDA receptor function. N-acetyl-cysteine (NAC), a glutathione precursor, was administered to patients to determine whether increased levels of brain glutathione would imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
227
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 328 publications
(239 citation statements)
references
References 63 publications
10
227
0
2
Order By: Relevance
“…If such activation of the IL-6/Nox2 pathway occurs in situations of genetically diminished brain-GSH levels, such as those described in some schizophrenia cohorts, it will lead to further decrease in GSH levels, NMDA-R hypofunction and increased oxidative damage to macromolecules and lipids (Do et al, 2009). Recent results showing that treatment with N-acetyl-cysteine, a precursor of GSH, improves negative symptoms, and corrects mismatch negativity in schizophrenia patients further support the idea of a redox imbalance in schizophrenia Lavoie et al, 2008).…”
Section: The Role Of Superoxide In the Persistent Effects Of Nmda-r Amentioning
confidence: 82%
“…If such activation of the IL-6/Nox2 pathway occurs in situations of genetically diminished brain-GSH levels, such as those described in some schizophrenia cohorts, it will lead to further decrease in GSH levels, NMDA-R hypofunction and increased oxidative damage to macromolecules and lipids (Do et al, 2009). Recent results showing that treatment with N-acetyl-cysteine, a precursor of GSH, improves negative symptoms, and corrects mismatch negativity in schizophrenia patients further support the idea of a redox imbalance in schizophrenia Lavoie et al, 2008).…”
Section: The Role Of Superoxide In the Persistent Effects Of Nmda-r Amentioning
confidence: 82%
“…NAC has been studied as an adjunctive treatment in schizophrenia in a recently completed 6-month, double-blind, randomized, placebo-controlled trial (n=140), which found significant advantages of NAC over placebo on several scales that include the Clinical Global Impressions (CGI) (effect size of 0.43), the Positive and Negative Symptoms Scale (PANSS) (effect size of 0.57) and the Barnes Akathisia Scale (BAS) (effect size of 0.44) (Berk et al, unpublished observations). In a subset of patients enrolled in this study (n=11), NAC was also associated with an increase in plasma glutathione and the amelioration of mismatch negativity, an auditory evoked potential component characteristically impaired in schizophrenia, which may indicate the ability of NAC to correct more fundamental neurophysiological dysfunction (Lavoie et al, 2007).…”
Section: N-acetylcysteinementioning
confidence: 99%
“…In this context, it is also important to note that activation of mGluRs reduces the loss of cellular GSH (Sagara and Schubert, 1998). Interestingly, antioxidants including omega-3 fatty acids (Sivrioglu et al, 2007) and NAC have already demonstrated clinical efficacy in the treatment of schizophrenia symptoms (Berk et al, 2008a;Lavoie et al, 2008), obsessive-compulsive disease (Grant et al, 2009;Odlaug and Grant, 2007), and bipolar disorder (Berk et al, 2008b). Our findings provide a rationale for this treatment effect and suggest a therapeutic option for the therapy of G72-associated psychiatric disorders.…”
Section: Discussionmentioning
confidence: 99%